Utopia „nie inności” w niepełnosprawności. Na marginesie rozważań o sztuce osób niepełnosprawnych - Nieduziak, Edyta (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
The use of the concept of disability entails the construction of models of this phenomenon. The most common of these are extreme models: medical and social. They are used by representatives of various communities, including those involved in artistic creativity. Is there any connection between the practice of art and disability? Despite the slogans that „anyone can be an artist” and „disability does not determine the artistic activity”, „creative freedom” and „equality before the art”, it turns out that certain models of disability are accepted. This article tries to show, on the example of two artists: Maria Wnęk and Frida Kahlo, different ways of looking at the art of disabled people depending on contexts and accordingly giving them different meanings to the images they created.
Keywords: art brut; artistic creation of disabled people; disability; model of disability